2008
DOI: 10.1002/anie.200804194
|View full text |Cite
|
Sign up to set email alerts
|

How Rigid Rods Self‐Assemble at Curved Surfaces

Abstract: Spherical or low-aspect-ratio particles have been used for producing superstable foams by tuning the particle wettability and interparticle interactions. [1][2][3][4][5][6][7][8][9] What is remarkable about these foams is that the stabilization against disproportionation arises from jamming in the adsorbed particle layer at a bubble surface, [10][11][12][13] rather than solidification or gelling of the continuous phase. Realizing the importance of particle shape, Alargova et al. [10,14,15] have developed a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
(32 reference statements)
1
44
0
Order By: Relevance
“…a third of the persistence length of the rod. 36 In agreement with these expectations, neither large-scale interfacial protein-particle aggregates nor correlated rigid-like motion of particle clusters (as it would be expected for fibrils bridging between particles) have ever been observed under the microscope, confirming the absence of fibril-particle coupling. Experiments at various bulk concentrations of fibrils (c # 0.1% w/v) were carried out in a home-designed microscopy cell consisting of an epoxy resin micro-well of 1.5 cm diameter and 150 mm thickness (Fig.…”
Section: Resultssupporting
confidence: 67%
“…a third of the persistence length of the rod. 36 In agreement with these expectations, neither large-scale interfacial protein-particle aggregates nor correlated rigid-like motion of particle clusters (as it would be expected for fibrils bridging between particles) have ever been observed under the microscope, confirming the absence of fibril-particle coupling. Experiments at various bulk concentrations of fibrils (c # 0.1% w/v) were carried out in a home-designed microscopy cell consisting of an epoxy resin micro-well of 1.5 cm diameter and 150 mm thickness (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Ultrastable foams stabilized by these rods have hair-like structures, in which rods are bent and entangled at the bubble surfaces. Zhou et al [19] have reported the production of superstable foams with bimodal size distribution stabilized by modified CaCO 3 particles. The rigidity and high ratio of CaCO 3 rods result in the first examples of unique bubble surface structures that evolve as a function of the curvature from nestlike to armorlike.…”
Section: Introductionmentioning
confidence: 98%
“…These may fill the role of a cheaper or less toxic alternative to surfactants, or they may be customized to include additional desirable properties. Examples include ferromagnetic particles [4,5] (which can be detected remotely), Janus particles [6][7][8][9] (having different interfacial properties on different parts of their surface, improving their stabilization properties), or particles with nonspherical geometries [10][11][12][13][14] (which introduce additional geometrical degrees of freedom and also exhibit improved stabilization properties).…”
Section: Introductionmentioning
confidence: 99%